Advances in survival analysis - Balakrishnan, N., 1956-; Rao, C. Radhakrishna (Calyampudi Radhakrishna), 1920-2023 (Handbook of statistics (Amsterdam, Netherlands) ;, 2004)
The book covers all important topics in the area of Survival Analysis. Each topic has been covered by one or more chapters written by internationally renowned experts. Each chapter provides a comprehensive and up-to-date review of the topic. Several new illustrative examples have been used to demonstrate the methodologies developed. The book also includes an exhaustive list of important references in the area of Survival Analysis. Includes up-to-date reviews on many important topics. Chapters written by many internationally renowned experts. Some Chapters provide completely new methodologies and analyses. Includes some new data and methods of analyzing them.